2018
DOI: 10.1111/1754-9485.12725
|View full text |Cite
|
Sign up to set email alerts
|

Optimising motivation and reducing burnout for radiation oncology trainees: A framework using self‐determination theory

Abstract: Radiation oncology trainees in Australia and New Zealand have relatively high levels of emotional exhaustion and depersonalisation which are core components of burnout. The stresses of a demanding clinical load, studying for exams as well as family commitments are all contributing factors. Self-Deter mination Theory (SDT) provides a framework for optimising motivation which may be intrinsic or extrinsic. The three core components of SDT are competence, relatedness and autonomy. These factors should be addresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Although this census did not specifically deal with this subject, questions about sources of stress and the value of mentoring are related to this area. There is now information on the prevalence and measures to reduce burnout and emphasis which is beyond the scope of the census …”
Section: Discussionmentioning
confidence: 99%
“…Although this census did not specifically deal with this subject, questions about sources of stress and the value of mentoring are related to this area. There is now information on the prevalence and measures to reduce burnout and emphasis which is beyond the scope of the census …”
Section: Discussionmentioning
confidence: 99%
“…In this edition, Michael and Anne Poulsen have written a very interesting and relevant article about burnout …”
mentioning
confidence: 99%
“…Indeed, in radiation oncology, there are now studies that have shown burnout prevalence in academic chairs of radiation oncology, residency program directors, radiation oncologists and trainees. This is why Michael Poulsen's article is important as it is the next step . Its’ focus is specifically on radiation oncology trainees.…”
mentioning
confidence: 99%
See 2 more Smart Citations